Program Linear Menggunakan Metode Grafik - Julianis (Jurnal Pustaka Cendekia Pendidikan, 2025)
Linear programming is part of Operation Research which studies optimum problems. The principles of linearprogramming are applied to real problems including in the fields of economics, health, education, trade,transportation, industry, social affairs, and others. a linear programming problem is a problem related tofinding the optimal value (maximum or minimum value) of the objective function (which is a linear function inthe form Z=c_1x_1+c_2x_2+…c_nx_n\ with decision variables x_1, x_2,…, x_n depending on theconstraints/problem constraints which are expressed in the form of linear equations or inequalities. Theconstraints/problem constraints are referred to as constraints functions, the decision variables on linearprogramming problems must be non-negative x_1 ≥ 0, i = 1,2,…,n.The set of points that fulfill the constraintfunction and the requirements of the (non-negative) decision variable is referred to as the feasible region.Anypoint in the feasible solution area that yields the optimum value (maximum or minimum) of the objectivefunction is referred to as the optimum solution.Graphic method is a way that can be used to solve optimizationproblems in linear programming.The limitation of this method is that the variables that can be used are limited(only two), the use of 3 variables will be very difficult to do.